Redescription of Bactronophorus thoracites Gould (1856) and Bankia gracilis Moll (1935) from Sabah Waters, Malaysia, with Short Ecological Notes and Measurements Metrics - Loo Zhen Ann; Chen Cheng Ann; Khairul Adha Abd Rahim; Farah Diba (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • Redescription of marine woodborers, Bactronophorus thoracites and Bankia gracilis from the region were illustrated. • New records of Bactronophorus thoracites and Bankia gracilis from the region. • Addition info on the measurements of pallets was recorded. • Certain ecological data on the habitat of marine woodborers Bactronophorus thoracites and Bankia gracilis were documented.